2002
DOI: 10.1112/s0024609301008736
|View full text |Cite
|
Sign up to set email alerts
|

On the Zero Modes of Weyl–dirac Operators and Their Multiplicity

Abstract: It is proved that the existence of zero modes of Weyl-Dirac operators is a rare phenomenon. An estimate of the multiplicity is given in term of the magnetic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 9 publications
1
24
0
1
Order By: Relevance
“…See Balinsky and Evans [5]. The paper by Fröhlich, Lieb and Loss [12] revealed that the existence of zero modes of a Weyl-Dirac operator plays a crucial role in the study of stability of Coulomb systems with magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…See Balinsky and Evans [5]. The paper by Fröhlich, Lieb and Loss [12] revealed that the existence of zero modes of a Weyl-Dirac operator plays a crucial role in the study of stability of Coulomb systems with magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…The first objective of the research reported here was to confirm that the results in [1] can be extended to Dirac-type operators with matrixvalued potentials. This then set the scene for the main goal which was to determine the decay rates of zero modes whenever they occur.…”
Section: Introductionmentioning
confidence: 91%
“…Assuming that Q(·) C 4 ∈ L 3 (R 3 ), where · C 4 denotes any matrix norm on C 4 , it was shown that Q is a small perturbation of α · p and hence (1.1) defines a self-adjoint operator H as an operator 4 with weak first derivatives in (L 2 (R 3 )) 4 . The technique in [1] readily applied to (1.1) to meet the first objective and yield the following result:…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fields B ∈ B ES are smooth and satisfy bounds of the form |B(x)| = O(|x| −4 ) as |x| → ∞, while it is always possible to find a smooth potential A with B = dA which satisfies the bounds of the form |A(x)| = O(|x| −3 ) as |x| → ∞. It follows that fields in B ES (and their associated potentials) fall into the classes considered in [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Most early works concentrated on the construction of explicit examples, including the original example [17], examples with arbitrary multiplicity [2], compact support [6] and a certain rotational type of symmetry ( [10]; further details below). Some subsequent work moved towards studying the set of all zero mode producing fields (or potentials) within a given class; in particular, this set is nowhere dense [4,5] and is generically a sub-manifold of co-dimension one ( [7]; slightly different classes of potentials were considered in these works).…”
Section: Introductionmentioning
confidence: 99%